The prospective study of the effect of Nd:YAG laser iridectomy in patients with relative pupillary block on the retina central zone according to the data of optical coherence tomography - A. F. Fakhrutdinova; A. V. Ardamakova; N. A. Fedoruk; A. V. Bolshunov (Сибирский научный медицинский журнал, 2020)
Objective: To assess possible changes in the macular region of the retina and the thickness of the peripapillary retinal nerve fiber layer (RNFL) according to the results of a dynamic study of OCT parameters after Nd:YAG laser iridectomy in patients with relative papillary block. Material and methods. Optical coherence tomography (OCT) was performed in 28 patients (38 eyes) with a relative papillary block before and after 1 hour, 1 day, 3 days, 1 week, 1 and 6 months after Nd:YAG laser iridectomy. We analyzed changes in the thickness of the retina in 9 standard zones according to ETDRS, the thickness of the layer of ganglion cells and the peripapillary RNFL. Results. The thickness of the layer of ganglion cells, as well as the thickness of the peripapillary RNFL, did not change significantly after laser intervention (all p ˃ 0.05) during the entire observation period. According to OCT, the retinal thickness significantly increased an hour after Nd:YAG laser iridectomy in 5 zones out of 9 by ETDRS and continued to increase over the course of a day. After 1 week, the thickness of the retina returned to its original values and did not change throughout the observation period. Conclusion: In patients with the relative papillary block, Nd:YAG laser iridectomy has a negligible effect on the thickness of the retina, measured by OCT, does not fundamentally affect the thickness of the layer of ganglion cells and the thickness of the peripapillary RNFL, and is safe for the central zone of the retina.